Defects in plant immunity modulate the rates and patterns of RNA virus evolution. Issue 2 (20th June 2022) - Navarro, Rebeca; Ambrós, Silvia; Butković, Anamarija; Carrasco, José L; González, Rubén; Martínez, Fernando; Wu, Beilei; Elena, Santiago F
Abstract: It is assumed that host genetic variability for susceptibility to infection conditions virus evolution. Differences in host susceptibility can drive a virus to diversify into strains that track different defense alleles (e.g. antigenic diversity) or to infect only the most susceptible genotypes. Here, we have studied how variability in host defenses determines the evolutionary fate of a plant RNA virus. We performed evolution experiments with Turnip mosaic potyvirus in Arabidopsis thaliana mutants that had disruptions in infection-response signaling pathways or in genes whose products are essential for potyvirus infection. Plant genotypes were classified into five phenogroups according to their response to infection. We found that evolution proceeded faster in more restrictive hosts than in more permissive ones. Most of the phenotypic differences shown by the ancestral virus across host genotypes were removed after evolution, suggesting the combined action of selection and chance. When all evolved viral lineages were tested in all plant genotypes used in the experiments, we found compelling evidences that the most restrictive plant genotypes selected for more generalist viruses, while more permissive genotypes selected for more specialist viruses. Sequencing the genomes of the evolved viral lineages, we found that selection targeted the multifunctional genome-linked protein VPg in most host genotypes. Overall, this work illustrates how different host defenses modulate the rates and extent of virus evolution.